Perbandingan Pelarut Etanol Dengan Etil Asetat Terhadap Aktivitas Antibakteri Ekstrak Kulit Buah Salak (Salacca Zalacca Reinw) Pada Pertumbuhan Bakteri Staphylococcus Aureus ATCC 25923 - Wahyuni, Umi Nurul; Sihotang, Yosua Maranatha; Marpaung, Mauritz Pandapotan; Prasetyo, Dani (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Staphylococcus aureus is one of the most common bacteria causing infections in the world. One way to treat infections caused by S. aureus is by giving antibiotics. However, recently there have been many reports regarding antibiotic resistance. Efforts that can be made to deal with this resistance are using  natural  antibiotic  ingredients,  for  example  the  skin  of  the  zalacca (Salacca zalacca Reinw). This study aims to determine the difference between ethanol extract and ethyl acetate extract of the skin of zalacca (Salacca zalacca Reinw) against the antibacterial activity of Staphylococcus aureus. Salak fruit peel was extracted by maceration method using two solvents, namely ethanol and  ethyl  acetate.  The  extract  obtained  was  then  tested  for  antibacterial activity. The yield of the ethanol extract of the bark was higher, namely 1.57% compared to the ethyl acetate extract of 0.68%. The ethanol extract of the skin of the zalacca fruit has  higher antibacterial activity than the ethyl  acetate extract against Staphylococcua aureus bacteria.